A Rare Case of Isolated Atrial Myocarditis Causing Death With no Post Mortem Computed Tomography Scan Correlation. (June 2018) - Tse, Rexson; Garland, Jack; Kesha, Kilak; Triggs, Yvonne; Modahl, Lucy; Milne, David; Yap, Zhi; Stables, Simon
Abstract : Abstract: Acute myocarditis is a potentially fatal cardiac pathology that is thought to cause sudden death through arrhythmia and cardiac failure. Of the different subtypes, lymphocytic myocarditis is the most common form. The pathophysiology of myocarditis can be generally diffuse or focally involve the ventricles, but less frequently affects the atria. Although the clinical literature reports isolated atrial myocarditis as a cause of atrial fibrillation and enlargement, there is scant postmortem literature on the findings of this pathology. We report a fatal case of isolated lymphocytic atrial myocarditis affecting only the left atrium in a 56-year-old man, where microscopy of the left atrium confirmed a florid lymphocytic myocarditis. Retrospective postmortem computed tomography scan review did not show any abnormalities on the left atrial wall.